Predictors of Mortality among Low-Birth-Weight Neonates Admitted to Neonatal Intensive Care Unit - Munir, Minahil; Mushtaq, Misbah; Shaukat, Rabia; Tehreem, Ammara; Fazal, Fariha; Khurshid, Asim (Biological and Clinical Sciences Research Journal, 2025)
Low birth weight (LBW) is defined as a birth weight less than 2.5 kg and is a major contributor to neonatal morbidity and mortality worldwide. Identification of maternal and perinatal predictors of mortality is essential for implementing targeted interventions to improve survival. Objective: To determine the predictors of mortality among low-birth-weight neonates admitted to the neonatal intensive care unit (NICU). Methods: A prospective cohort study was conducted in the Department of Pediatric Medicine, Children’s Hospital Multan, from February 2024 to July 2024. A total of 114 neonates aged 1–7 days who met the inclusion criteria were enrolled after parental consent was obtained. Baseline characteristics, including maternal age, gravidity, area of residence, neonatal age, gender, and birth weight, were recorded. Maternal factors (diabetes, pregnancy-induced hypertension), perinatal characteristics (place of delivery, APGAR score), and the need for resuscitation at birth were documented. Neonates were followed for 28 days to record mortality. Data were analyzed using SPSS v23. Continuous variables were expressed as mean ± SD, and categorical variables as frequencies and percentages. Mortality predictors were assessed using relative risk with 95% confidence intervals. Results: Among 114 neonates, 21 (18.4%) died within 28 days. Maternal diabetes, low APGAR score (<7), and need for resuscitation were associated with higher mortality. Other factors such as gender, area of residence, pregnancy-induced hypertension, and place of delivery showed no statistically significant association. Conclusion: Mortality among LBW neonates remains high, with APGAR score, maternal diabetes, and resuscitation need serving as important predictors. Early identification and intervention targeting these risk factors may reduce neonatal deaths.